STATISTICAL ANALYSIS OF LOAN PORTFOLIO AND ITS MANAGEMENT IN BANKS (Academicia Globe: Inderscience Research, 2023)
The article analyzes the existing work on the issue of dealing with credit portfolios and problem loans in the banking system and the measures taken within the framework of the legislation, as well as some recommendations on ensuring the effective operation of the lending and collection system in this area. given.